IMPLEMENTATION OF DIENES BLOCKS IN MATHEMATICS LEARNING IN PRIMARY SCHOOLS - Dyah Anungrat Herzamzam; Nurmulia Diniarti; Chrisnaji Banindra Yudha (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research purpose to increase mathematics learning outcomes through the Dienes Block at SDN Pisangan Timur 05, East Jakarta. This Classroom Action Research was carried out in 3 cycles, where in each cycle there were 4 stages including: a.) Planning, b.) Implementation (Action), c.) Observation, and d.) Reflection. The results of this research show that there has been an increase in mathematics learning outcomes which can be seen from the implementation of research in each cycle. Mathematics learning outcomes can be seen from the score obtained before the class average of 65.05 (only 10 students reached the school's KKM, namely 75) in the low category, in the first cycle it increased to 72.05 (only 17 students reached the KKM) with the medium category, and in cycle II it increased to 78.03 (only 22 students reached the KKM) with the very high category. The increase in student mathematics learning outcomes can be seen from the majority of students being more active in working on LKPD in groups, and students communicating with each other in solving mathematics problems.